ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KEBIJAKAN PENGUNGKAPAN INFORMASI SOSIAL DAN LINGKUNGAN (Studi Empiris Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2008-2012) - Andi Rachmanda; Fuad Fuad (Diponegoro Journal of Accounting, 2014)
The purpose of this study was to examine the effect of corporate governance mechanisms on the policy of social and environmental disclosure. Indicators used to measure corporate governance mechanisms in this study is the proportion of independent board, the structure of the Chief Risk Officer (CRO), managerial ownership, board size, independence of the audit committee, the board of commissioners meeting frequency, as well as the nomination and remuneration committee. While social and environmental disclosure as the dependent variable was measured using amount disclosure items appropriate with the Global Reporting Initiative (GRI) G3.1 index. In addition, this study also added two control variables are firm size firm size and leverage. This study uses secondary data with entire population of banking companies listed in the Indonesia Stock Exchange (BEI) in 2008-2012. The method used to determine the sample using purposive sampling. The analytical method used is multiple linear regression, regression testing prior to first tested the classical assumptions. The results of hypothesis testing showed that the proportion of independent board negatively affects the social and environmental disclosure. Other results noted that the structure of the CRO, managerial ownership, as well as the nomination committee and remuneration positive effect on social and environmental disclosure. While the size of the board of directors, audit committee independence, and the frequency of meetings of the board of commissioners did not significantly affect disclosure